1998
DOI: 10.1074/jbc.273.17.10411
|View full text |Cite
|
Sign up to set email alerts
|

Residues 21–30 within the Extracellular N-terminal Region of the C5a Receptor Represent a Binding Domain for the C5a Anaphylatoxin

Abstract: The functions of the C5a anaphylatoxin are expressed through its interaction with a cell-surface receptor with seven transmembrane helices. The interaction of C5a with the receptor has been explained by a two-site model whereby recognition and effector sites on C5a bind, respectively, to recognition and effector domains on the receptor, leading to receptor activation (Chenoweth, D. E., and Hugli, T. E.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
44
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 44 publications
10
44
0
Order By: Relevance
“…The incomplete cysteine dependence of the C receptors suggests that the unpaired C5a sulfhydryl was only contributing part of the N-terminal receptor binding energy, and that there was additional selective pressure to retain endogenous binding elements. Consistent with this hypothesis, we note that the residues believed to contribute most of the binding energy, C5aR positions 20 -30 (11,12), were relatively highly conserved in the C receptors, as compared with the rest of the N terminus (Fig. 5).…”
Section: Use Of C5a C27r/r40c To Trap Interactions With the C5ar Nt-c5asupporting
confidence: 71%
See 1 more Smart Citation
“…The incomplete cysteine dependence of the C receptors suggests that the unpaired C5a sulfhydryl was only contributing part of the N-terminal receptor binding energy, and that there was additional selective pressure to retain endogenous binding elements. Consistent with this hypothesis, we note that the residues believed to contribute most of the binding energy, C5aR positions 20 -30 (11,12), were relatively highly conserved in the C receptors, as compared with the rest of the N terminus (Fig. 5).…”
Section: Use Of C5a C27r/r40c To Trap Interactions With the C5ar Nt-c5asupporting
confidence: 71%
“…Conversely, the small molecule L-584,020 competes with full-length C5a but not with hexapeptides (8), suggesting that L-584,020 inhibits binding but not activation. Furthermore, NMR spectroscopy has shown that the structure of the isolated C5aR N terminus is altered by incubation with C5a, suggesting that the N terminus of the receptor interacts with the ligand (11). Because hexapeptide analogs such as W5Cha are full agonists for the C5aR, the first site is apparently not a key component of the switch mechanism (8,(11)(12)(13)(14).…”
mentioning
confidence: 99%
“…Although in a linear polypeptide this would correspond to a distance of roughly 17.5 Å, these residues form a loop in the crystal structure of rhodopsin (3), bringing them considerably closer together. NMR spectroscopic studies of C5aR fragment 1-34 showed nonsequential nuclear Overhauser effect connectivities in the region 20 -30, confirming that some folded conformation is present in this region (26). Furthermore, the receptor N terminus may be conformationally flexible.…”
Section: Discussionmentioning
confidence: 68%
“…Approximately half of the binding energy for C5a appears to be derived from interactions with the receptor N terminus (25). NMR studies showed that a peptide identical to the first 34 amino acids of C5aR retained its ability to bind C5a and that proton resonances in receptor positions 21-30 were most strongly affected by the binding event (26). Although these data implicate the N terminus of the C5aR in ligand binding, it remains unclear which region of C5a is involved in the interaction.…”
Section: G Protein-coupled Receptors (Gpcrs)mentioning
confidence: 82%
“…For the C5a receptor, although the ligand-binding site was assigned to residues 21-30 in NT, a deletion of residues 1-22 abolished signaling (59), like the ⌬2-9 deletion in our study. The first residues of NT of CXCR4 could be actually part of site II, possibly interacting with the extracellular loops, as has been proposed for the C5a receptor (60). Alternatively, residues 2-9, although not essential for access of the chemokine to site I, may be required for its proper orientation toward site II, and thus for signaling.…”
Section: Role Of Third Intracellular Loop In Signal Transduction-mentioning
confidence: 99%